Pore formation by LamB of Escherichia coli in lipid bilayer membranes. - Benz, R (1986)
Lipid bilayer experiments were performed in the presence of different Escherichia coli LamB preparations. These LamB preparations formed two types of pores in the membranes. Large pores, which had a single-channel conductance of 2.7 nS and comprised about 1 to 6% of the total pores, were presumably contaminants which might have been induced together with LamB. LamB itself formed small pores with a single-channel conductance of 160 pS in 1 M KCl. These pores could be completely blocked by the addition of maltose and maltodextrins. Titration of the pore conductance with maltotriose suggested that there was a binding site inside the pores with a Ks of 2.5 X 10(-4) M for maltotriose. On the basis of our data we concluded that the structure of the LamB channels is quite different from the structures of the channels of general diffusion porins, such as OmpF and OmpC.